Traditional Measurement Units of the Dayak Desa in Rice and Paddy Transactions: Conversion to the Modern Metric System - Pelipa, Emilia Dewiwati; Marganingsih, Anna; Bobi, Yopinus; Astikawati, Yunita (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2026)
This study examines the traditional measurement system used by the Dayak Desa community in rice and paddy transactions, with a focus on its cultural significance and conversion into modern metric units. In this community, rice is not only a staple commodity but also functions as a socio-economic instrument embedded in cultural practices, including barter systems, customary obligations, and daily exchanges. The persistence of traditional measurement units—gatang, mok, and kulak—reflects the integration of economic activities with local knowledge and cultural values. This research employs a qualitative descriptive approach supported by simple quantitative analysis. Data were collected through in-depth interviews, participant observation, and documentation involving customary leaders, farmers, and local traders in Sintang Regency, West Kalimantan. Quantitative measurements were conducted using digital scales to determine the conversion of traditional units into kilograms and liters. Data analysis was carried out using the interactive model of Miles and Huberman, combined with empirical averaging techniques for measurement conversion. The findings reveal that the traditional measurement system is structured hierarchically according to transaction scale, where gatang is used for small quantities, mok for medium transactions, and kulak for large volumes. Empirical results indicate that one gatang is equivalent to approximately 0.20 kilograms (0.25 liters), one mok to 0.25 kilograms (0.30 liters), and one kulak to 2.5 kilograms (3 liters). These results demonstrate that traditional measurement practices possess internal consistency and can be reliably converted into standardized metric units. The study contributes to the literature by integrating ethnometrology and economic perspectives, highlighting how traditional measurement systems can coexist with modern standards. Practically, the conversion framework reduces information asymmetry and enhances fairness in market transactions. The study concludes that preserving traditional measurement systems while enabling their compatibility with modern metrics is essential for sustaining cultural identity and improving economic integration in rural communities